PENDAMPINGAN ORANG TUA PADA ANAK USIA DINI PADA MASA PANDEMI - Citra Amalia; Nurhayani Nurhayani; Khadijah Khadijah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The Covid-19 pandemic requires children to study at home. All student learning activities are carried out at home with guidance from parents. So that the role of parents in educating children is in the first place. Parents are the main responsibility for the education of their children. The purpose of writing this article is to see how the efforts made by parents in accompanying their children during the pandemic. The research method used in this research is descriptive qualitative method. The method is, the method used is based on data obtained from the research field. In this study, besides wanting to see the child's learning process, the role and parenting pattern or mentoring of parents to their children during online learning that you want to observe carefully. Parents can apply teaching methods that involve daily activities such as making food, cleaning the house, or other things that can be created with the material being studied by the child. From the results of research on the role of parents in accompanying children during online learning, they still find various obstacles ranging from a lack of understanding of the condition of each child.